A New Species of Predaceous Mites of the Genus Amblyseiella (Parasitiformes, Phytoseiidae) from Ukraine - Kolodochka, L.A.; Omeri, I.D. (Вестник зоологии, 2010)
A new species of phytoseiid mites Amblyseiella antonii Kolodochka et Omeri, sp. n. (Parasitiformes, Phytoseiidae) found on Juniperus sabina L. in Kyiv (Ukraine) is described. This is the first record of a representative of the genus Amblyseiella Muma from Ukraine. Description, drawings, measurements and diagnosis of the species are given.